World Economic Outlook, October 1990. (World Economic Outlook; World Economic Outlook ;, 1990)
This paper highlights that after several years of rapid expansion that brought many countries to historically high levels of resource utilization, the growth of the world economy is projected to slow to about 2 percent in 1990 from 3 percent in 1989. The global slowdown would reflect a moderation of growth in both industrial and developing countries and a contraction of output in Eastern Europe and in the Union of Soviet Socialist Republics. In 1991, the expansion in world output is expected to pick up to 2 1\2 percent, reflecting stronger growth in developing countries.